2016
DOI: 10.4250/jcu.2016.24.4.294
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Fat Thickness and Neutrophil to Lymphocyte Ratio are Increased in Non-Dipper Hypertensive Patients

Abstract: BackgroundIn this study, we aimed to investigate the relationship between echocardiographic epicardial fat thickness (EFT), neutrophil to lymphocyte ratio (NLR; an important inflammatory marker), and diurnal blood pressure (BP) changes in patients with recently diagnosed essential hypertension.MethodsA total of 647 patients underwent echocardiography and 24 hours of ambulatory BP monitoring. EFT was measured by echocardiography, while NLR was measured by dividing the neutrophil count by the lymphocyte count. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…Ozcicek et al (39) showed that NLR levels were independently associated with EFT in patients with end-stage renal disease receiving hemodialysis. Another study found that NLR and EFT were increased in non-dipper hypertensive patients and they were significantly correlated with each other (40). In the present study, although patients with more complex CAD had significantly higher levels of NLR, we did not find any correlation between NLR and EFT.…”
Section: Discussioncontrasting
confidence: 86%
“…Ozcicek et al (39) showed that NLR levels were independently associated with EFT in patients with end-stage renal disease receiving hemodialysis. Another study found that NLR and EFT were increased in non-dipper hypertensive patients and they were significantly correlated with each other (40). In the present study, although patients with more complex CAD had significantly higher levels of NLR, we did not find any correlation between NLR and EFT.…”
Section: Discussioncontrasting
confidence: 86%
“…Still another limitation is that because we did not take serial blood samplings during and after treatment period, we could not determine whether COP-NLR’s interval changes predicted treatment response and survival or establish its possible role in post-treatment surveillance. In addition, it is worth noting that, although blood parameters are of clinical value in predicting disease severities of the associated complications of common disorders such as diabetes mellitus 37 and hypertension, 38 we did not exclude patients with these comorbid conditions as our sample size was already limited and we lacked detailed information regarding their disease severity. Nonetheless, the confounding impact of these comorbidities should be minimized as CCIS was one of risks we factored into our survival analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In another recent study, it was shown that local EFT may play a role in the pathogenesis of ventricular arrhythmias originating from the right ventricular outflow tract [23,24]. EFT was associated with abnormal diurnal BP patterns [25]. As can be observed, EFT is associated with many clinical cardiovascular conditions.…”
Section: Discussionmentioning
confidence: 89%